PELATIHAN DESAIN GRAFIS CORELDRAW DALAM MENUMBUHKAN JIWA WIRAUSAHA WARGA BELAJAR PROGRAM KESETARAAN DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) TIM SUARA MASYARAKAT DAWUAN CIKAMPEK - Endriani, Mutiara Citra; Meilya, Ika Rizqi; Santika, Tika (Comm-Edu (Community Education Journal), 2025)
Departing from the need to enhance the practical skills of equivalency program learners in relation to entrepreneurship, this study aims to analyze and describe the implementation of CorelDraw-based graphic design training at PKBM Tim Suara Masyarakat Dawuan Cikampek in fostering entrepreneurial character. The research was conducted using a qualitative-descriptive approach with a case study method, supported by data collection techniques such as interviews, observations, and documentation. Informants included training organizers, instructors, and learners. The results showed that the training was carried out in three stages: pre-training, implementation, and evaluation. Supporting factors such as instructor competence, structured training design, relevant material, and learner motivation contributed to the success of the program. The findings indicate that the training positively influenced the development of entrepreneurial traits among learners, including selfconfidence, responsibility, risk-taking, leadership, originality, and future orientation. The main challenge identified was related to technological changes and participants' limited access to appropriate devices. Therefore, similar training programs should be developed sustainably and be responsive to technological developments to ensure that learners are equipped to face entrepreneurial challenges in the digital era.